Following the spectral and spin evolution of the longest-lived post-nova SSS - Vasilopoulos, Georgios (2020)
1RXS J050526.3-684628 is a super soft source in the Large Magellanic Cloud(LMC). A recent study reported the discovery of coherent pulsations,and identified the system as an accreting White Dwarf (WD). Moreover, thestudy of historic X-ray and optical properties of J050526 have revealedit to be a remarkably long-lived post-nova SSS (~30 year duration),reaching its peak flux around 2013. Nevertheless, the lack of multipledeep X-ray observations hampers the study of the system and prohibitsfurther testing of theoretical models. We request a 60 ks XMM-Newtonobservation to study the evolution of its spectral and temporal propertiesduring the decay of its flux.